A Systematic Journal Review on the Implementation of Lean Hospitals in Developing Countries - Dony Kurniadi Wibowo; Sutopo Patria Jati; Ayun Sriatmi (Universitas Ibn Khaldun Bogor, 2026)
Healthcare services in developing countries face persistent challenges such as limited resources, suboptimal service quality, and high workloads. To address these issues, the Lean Hospital approach has emerged as a strategic innovation aimed at improving efficiency and service quality by reducing waste. However, its implementation is frequently hindered by a lack of understanding, resistance stemming from organizational culture, and insufficient trained personnel. This necessitates a systematic examination to explore prevailing trends, identify facilitators and barriers, and develop an implementation model tailored to the specific needs of developing countries. This study adopts a Systematic Literature Review (SLR) methodology to evaluate Lean Hospital implementation across developing countries. Following rigorous stages of planning, execution, and reporting, a comprehensive search was conducted using databases such as PubMed, Scopus, ScienceDirect, and Google Scholar via Publish or Perish. Articles were screened based on inclusion criteria including topic relevance, publication date, language, accessibility, and journal accreditation. The PRISMA flowchart guided the selection process, yielding 27 articles for thematic analysis. The results highlight that Lean Hospital initiatives can substantially enhance operational efficiency and patient care quality, particularly through reduced waiting times and improved staff productivity. Key success factors include strong leadership commitment, a supportive organizational culture, and active staff participation. Nonetheless, significant barriers such as change resistance, resource limitations, and inadequate understanding of Lean principles must be overcome. Effective implementation requires contextual adaptation, technological integration, and continuous organizational capacity building. Ultimately, fostering a collaborative culture and patient-centered orientation is critical to achieving sustainable health system transformation in developing countries.